Agaro-oligosaccharides enhanced the Monilinia fructicola resistance of peach fruit by regulating antioxidative and phenylpropanoid metabolism - Li, Qian; Wei, Yingying; Chen, Yi; Jiang, Shu; Ye, Jianfen; Xu, Feng; Lou, Yongjiang; Ding, Phebe; Ouaziz, Meriem; Shao, Xingfeng (Elsevier, 2024)
Postharvest peach fruit is susceptible to Monilinia fructicola commomnly known as brown rot, which has caused significant economic losses in the peach industry. The objective of this study was to investigate the inhibitory effect of agaro-oligosaccharides on peach fruit against Monilinia fructicola, as well as its associated mechanisms. Results showed that agaro-oligosaccharides treatment did not affect the growth of Monilinia fructicola in vitro test and it did not have a significant influence on fruit quality. However, AO treatment led to a notable reduction in both disease incidence and lesion diameter in Monilinia fructicola-inoculated peach fruit. Agaro-oligosaccharides-treated fruit exhibited increased activities of superoxide dismutase, catalase, and ascorbic acid peroxidase with elevated expression levels of their respective genes as well as higher contents of ascorbic acid and glutathione. Furthermore, agaro-oligosaccharides increased the activities of chitinase and beta-1, 3-glucanase along with up-regulated gene expression levels. Increased activities of phenylalanine ammonia-lyase, cinnamate 4-hydroxylase, 4-coumarate coenzyme A ligase, polyphenol oxidase, and peroxidase, along with elevated expression levels of their corresponding genes, were also observed in agaro-oligosaccharides-treated fruit, resulting in the accumulation of total phenols, flavonoid, and lignin. These findings demonstrated that agaro-oligosaccharides induced the disease resistance of peach fruit, which was attributed to the activation of antioxidative and phenylpropanoid metabolism. © 2024 Elsevier B.V.